HANS GEORG GADAMER'S HERMENEUTICS VS BIBLICAL HERMENEUTICS: A COMPARATIVE ANALYSIS - Dina Elisabeth Latumahina; Gunaryo Sudarmanto (Manna Rafflesia, 2024)
At first, Hermeneutics as an interacting science was only used among the church as a method of Scripture Interpretation, with a standard system or method of hermeneutics. This hermeneutics is often referred to as Traditional Hermeneutics or Biblical Hermeneutics. However, in its development, Hermeneutics came out of biblical studies into the scope of philosophy, art, literature, and history. This hermeneutics is referred to as New Hermeneutics and appears in various variants. The purpose of this article is to introduce the New Hermeneutics system of the Postmodernist era, specifically Hans Georg Gadamer's Hermeneutics, and compare it objectively with the Biblical Hermeneutics System with the standard Grammatical-Historical method, which is often used to interpret the Bible. This study uses the comparative analysis study method to find fundamental similarities and differences between Hans Georg Gadamer's hermeneutic concepts and Biblical hermeneutics. Finally, the author makes conclusions and recommendations for Bible interpreters who are doing hermeneutics.